Vitamin D Status and Survival in Stage II-III Colorectal Cancer - Bao, Yichao; Li, Yaqi; Gong, Yan; Huang, Qianxia; Cai, Sanjun; Peng, Junjie (Frontiers in Oncology, 2020)
Vitamin D status has been shown to be positively correlated with the morbidity and prognosis of colorectal cancer (CRC) patients. However, the prognostic effect of vitamin D status on patients with stage II and III CRC, especially Asian patients, remains unclear. A total of 728 patients (523 in the primary cohort and 205 in the validation cohort) who were diagnosed with stage II-III CRC between January 2011 and December 2015 were enrolled. Their serum 25-hydroxyvitamin D3 [25(OH)D] levels were tested. Kaplan-Meier curves and Cox regression analyses were carried out. Subgroup analyses were conducted according to tumor location. In the primary cohort, the serum 25(OH)D level was positively correlated with the overall survival (OS) of all CRC patients (p= .016) and stage III patients (p= .009), while no correlation was found between 25(OH)D level and the prognosis of patients with stage II CRC. Moreover, 25(OH)D level was an independent prognostic factor for the OS of all patients with CRC [HR .541, 95% CI .334-.875, p=.012] and those with stage III CRC [HR .563, 95% CI .319-.993, p=.047]. Subgroup analysis indicated that only in the left-sided subgroup, stage III CRC patients with high 25(OH)D levels had better OS than those with low 25(OH)D levels [HR .474, 95% CI .230-.978, p=.043]. In the validation cohort, serum 25(OH)D levels were verified to have prognostic value for patients with stage III CRC [HR .220, 95% CI .080-.602, p=.003], and low 25(OH)D levels indicated worse OS for left-sided stage III CRC patients [HR .233, 95% CI .075-.727, p=.012]. In conclusion, vitamin D status is positively correlated with the survival of CRC patients, especially those with left-sided stage III CRC.